Separator for electrochemical device having improved compression resistance, electrochemical device including same, and method for manufacturing same
By applying small pore size uniformly distributed organic/inorganic composite coating and adhesive layer on the lithium-ion battery separation membrane, the problem of insufficient thermal shrinkage and bonding strength of lithium-ion batteries at high temperatures is solved, and the pressure resistance and life of the battery are improved.
Patent Information
- Application Number
- JP2024543547
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-04
- Filing Date
- 2023-07-05
- Publication Date
- 2025-02-12
- Estimated Expiration
- 2043-07-05
AI Technical Summary
The separation membrane of existing lithium-ion batteries has heat shrinkage under high temperature conditions, and the traditional organic/inorganic composite porous membrane is insufficient in the electrode assembly process, which is easy to separate, affecting the safety and life of the battery.
A porous polymer substrate is used, with an organic/inorganic composite porous coating and adhesive layer on the surface. The pore size of the coating is less than 40nm and is uniformly distributed. PVdF and acrylic adhesive are used to ensure the bonding strength and battery stability.
Improves the battery's resistance to deformation under pressure, reduces the risk of short circuit, extends battery life and reduces the risk of overvoltage.
Smart Images

Figure 2025504516000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention claims the benefit of the filing date of Patent Application No. 10-2022-0082782 filed with the Korean Intellectual Property Office on July 5, 2022 and the benefit of the filing date of Patent Application No. 10-2023-0086258 filed with the Korean Intellectual Property Office on July 4, 2023, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to a separator for an electrochemical device such as a secondary battery, an electrochemical device including the same, and a method for manufacturing the same. [Background technology]
[0003] Secondary batteries basically consist of a positive electrode, a negative electrode, a separator, and an electrolyte, and can be charged and discharged while chemical energy and electrical energy are reversibly converted. A representative example is the lithium-ion secondary battery. Lithium-ion secondary batteries are high-energy density energy storage devices and are widely used in small electronic devices such as mobile phones and laptops. In recent years, in response to environmental issues, high crude oil prices, and energy efficiency and storage, their application to hybrid electric vehicles (HEVs), plug-in electric vehicles (Plug-in EVs), electric bicycles (e-bikes), and energy storage systems (ESSs) has been rapidly expanding.
[0004] In the manufacture and use of such lithium secondary batteries, ensuring the safety of the lithium secondary battery is an important issue to be resolved. In particular, a separator commonly used in lithium secondary batteries exhibits extreme thermal shrinkage behavior under conditions such as high temperatures due to its material properties and manufacturing process properties, which may result in safety issues such as internal short circuits. Recently, in order to ensure the safety of lithium secondary batteries, an organic / inorganic composite porous separator has been proposed in which a mixture of inorganic particles and a binder is coated on a porous polymer substrate to form a porous coating layer. However, when an electrode and a separator are laminated to form an electrode assembly, there is a high risk that the electrode and the separator will separate from each other due to insufficient interlayer adhesion, and in this case, there is a problem that inorganic particles detached from the porous coating layer during the separation process may act as local defects in a lithium secondary battery element.
[0005] In order to solve these problems, it has been considered to further dispose an adhesive layer containing an adhesive binder resin to impart adhesive strength to the porous coating layer, but when both an organic / inorganic composite porous coating layer and an adhesive layer are disposed on the surface of a porous polymer substrate, there is a problem that the binder resin flows into the pores of the porous polymer substrate, thereby reducing the resistance. In addition, during the process of laminating the electrode when manufacturing an electrode assembly, the organic / inorganic porous coating layer may excessively press the polymer substrate or tear the polymer substrate, resulting in damage. Therefore, there is a growing demand for the development of a new separator having excellent adhesive strength to the electrode and durability. Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a separator for an electrochemical device having improved compression resistance. Another object of the present invention is to provide an electrochemical device including the separator. Another object of the present invention is to provide a method for manufacturing the separator. It will be readily apparent that other objects and advantages of the present invention can be achieved by the means or methods recited in the claims and combinations thereof. [Means for solving the problem]
[0007] A first aspect of the present invention relates to a separator for an electrochemical device, the separator comprising: a porous polymer substrate; a porous organic / inorganic composite porous coating layer disposed on at least one surface of the polymer substrate; and an adhesive coating layer disposed on one surface of the organic / inorganic porous coating layer, the opposite surface of the polymer substrate; the polymer substrate is a polymer membrane having an average pore size of 40 nm or less, and the pore distribution is such that a full width at half maximum (FWHM) value of a Gaussian distribution measured through a pore size distribution is 8.0 nm or less, the organic / inorganic composite porous coating layer comprises a particulate binder resin and inorganic particles, the particulate binder resin comprises an acrylic binder resin and a PVdF binder resin, and the adhesive coating layer comprises a PVdF binder resin.
[0008] In a second aspect of the present invention, in the first aspect, the polymer-based material has an air permeability of 100 sec / 100 cc or less and a resistance of 0.6 ohms or less.
[0009] In a third aspect of the present invention, in the first or second aspect, the separator has an air permeability of 100 sec / 100 cc or less and a resistance of 0.6 ohms or less.
[0010] A fourth aspect of the present invention is any one of the first to third aspects, wherein the polymer-based material has a porosity of 20 vol % to 50 vol %.
[0011] A fifth aspect of the present invention is any one of the first to fourth aspects, wherein the organic / inorganic composite porous coating layer contains the inorganic particles and the binder resin in a weight ratio of 75:25 to 90:10.
[0012] A sixth aspect of the present invention is any one of the first to fifth aspects, wherein the organic / inorganic composite porous coating layer is 100 wt % or more of a mixture of the inorganic particles and the binder resin.
[0013] A seventh aspect of the present invention is any one of the first to sixth aspects, wherein in the organic / inorganic composite porous coating layer, the PVdF-based binder resin and the acrylic-based binder resin are contained in a weight ratio of 30:70 to 5:95.
[0014] An eighth aspect of the present invention is any one of the first to seventh aspects, wherein the adhesive coating layer contains 90% by weight or more of the PVdF-based binder resin relative to 100% by weight of the entire adhesive coating layer.
[0015] In a ninth aspect of the present invention, in the eighth aspect, the PVdF-based binder resin of the adhesive coating layer has a weight average molecular weight of 600,000 or less.
[0016] A tenth aspect of the present invention is any one of the first to ninth aspects, wherein the PVdF-based binder resin of each of the organic / inorganic composite porous coating layer and the adhesive coating layer contains, as polymerization units, a copolymer of vinylidene fluoride and a monomer copolymerizable with vinylidene fluoride, and the copolymer contains 70 wt % or more of vinylidene fluoride.
[0017] An eleventh aspect of the present invention is the tenth aspect, wherein the PVdF-based binder resin has a degree of substitution by the monomer of 1 wt % to 40 wt %.
[0018] A twelfth aspect of the present invention is any one of the first to eleventh aspects, wherein the particulate binder resin is maintained in a particulate state within the separation membrane.
[0019] A thirteenth aspect of the present invention is any one of the first to twelfth aspects, wherein the thickness of the adhesive coating layer is 8% to 30% of the thickness of the organic / inorganic composite porous coating layer (100%).
[0020] A fourteenth aspect of the present invention relates to a method for producing a separation membrane according to any one of the first to thirteenth aspects, the method comprising:
[0021] (S10) preparing a porous polymer substrate; (S20) forming an organic / inorganic composite porous coating layer on a surface of the polymer substrate; and (S30) forming an adhesive coating layer on a surface of the organic / inorganic composite porous coating layer opposite to the surface on which the polymer substrate is disposed,
[0022] The step (S20) is carried out by dispersing inorganic particles and a particulate binder resin in an aqueous solvent as a dispersion medium to prepare a slurry for forming an organic / inorganic composite porous coating layer, applying the slurry onto the surface of the polymer substrate, and drying the slurry.
[0023] The step (S30) is carried out by dispersing a particulate binder resin in an aqueous solvent as a dispersion medium to prepare a composition for forming an adhesive coating layer, applying the composition on the surface of the organic / inorganic composite porous coating layer, and drying the composition. Effect of the Invention
[0024] The separator for an electrochemical device according to the present invention includes a polymer substrate having small and uniform pores, and includes a water-based organic / inorganic composite porous coating layer and an adhesive coating layer, and has an effect of improving compression resistance.
[0025] The separator may be damaged when pressure is applied to the electrode and separator during lamination by applying heat and pressure, and when pressure is applied inside the battery due to charging / discharging. In particular, in a portion where the thickness of the original sheet is significantly reduced locally, insulation is broken, resulting in a short circuit. If the pore characteristics of the separator are deformed, the path and speed of lithium ion movement change, affecting the life performance and rate-determining characteristics of the battery. In addition, if the separator is deformed to cause overvoltage, there is an increased possibility of lithium plating, in which the potential of the negative electrode drops rapidly to 0V. Therefore, by applying a separator with improved compression resistance, it is possible to have an effect of withstanding the applied pressure and suppressing the deformation of the separator. In particular, in the separator of the present invention, when pressure is applied, the coating layer structure acts as a buffer, thereby reducing the pressure applied to the porous substrate and suppressing the deformation of the separator.
[0026] The drawings attached to this specification are illustrative of preferred embodiments of the present invention and serve to facilitate a better understanding of the technical concept of the present invention together with the above-mentioned contents of the invention, and therefore the present invention should not be interpreted as being limited to only the matters shown in such drawings. Meanwhile, the shape, size, scale, ratio, etc. of elements in the drawings described in this specification may be exaggerated in order to emphasize a clearer description. [Brief description of the drawings]
[0027] [Figure 1] 1(a) is a schematic diagram showing a cross-sectional structure of a separation membrane according to one embodiment of the present invention, and FIG. 1(b) is a schematic diagram showing Example 1. FIG. [Diagram 2] 2 is a schematic diagram showing a cross-sectional structure of the separation membrane of Comparative Example 1. [Diagram 3] 2 is a schematic diagram showing a cross-sectional structure of the separation membrane of Comparative Example 2. [Figure 4] 1 is a schematic diagram showing a cross-sectional structure of a separation membrane of Comparative Example 3. [Diagram 5] 1 is a schematic diagram showing a cross-sectional structure of a separation membrane of Comparative Example 4. [Figure 6] This relates to the full width at half maximum (FWHM) of the pore size distribution (PSD) distribution, and the full width at half maximum can be expressed as the difference between two points, X2 and X1, on the x-axis, which correspond to 1 / 2 (1 / 2T) of the mode (T) on the y-axis. [Figure 7] The air permeability curves of the dry sample and the wet sample are shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] The present invention will be described in detail below. Prior to that, the terms or words used in the present specification and claims should not be interpreted limited to their ordinary or dictionary meanings, but should be interpreted with a meaning and concept that matches the technical idea of the present invention based on the principle that the inventor can appropriately define the concept of the term to best describe his / her invention. Therefore, it should be understood that the embodiments described in this specification and the configurations shown in the drawings are merely the most preferred embodiments of the present invention and do not fully represent the technical idea of the present invention, and therefore there may be various equivalents and modifications that can replace them at the time of this application.
[0029] Throughout the specification of this application, when a part is said to "comprise" certain elements, this means that it can further include other elements, rather than excluding other elements, unless specifically stated to the contrary.
[0030] In addition, the terms "about," "substantially," and the like, used throughout the specification of this application, when the manufacturing and material tolerances inherent in the referred meaning are given, are used to mean a numerical value or a approximation thereof, and are used to prevent unconscionable infringers from unfairly taking advantage of the disclosure in which precise or absolute numerical values are mentioned to aid in the understanding of this application.
[0031] Throughout the specification of this application, the phrase "A and / or B" means "A or B, or both."
[0032] Certain terminology has been used in the detailed description of the invention which follows for convenience only and is not limiting. The words "right", "left", "top" and "bottom" designate directions in the drawings to which reference is made. The words "inwardly" and "outwardly" designate directions toward or away from the geometric center of the designated device, system and components thereof, respectively. "Front", "rear", "upper", "lower" and related words and phrases designate locations and orientations in the drawings to which reference is made and are not intended to be limiting. Such terms include the words enumerated above, derivatives thereof and words of similar import.
[0033] The present invention relates to a separator for an electrochemical device. In the present invention, the electrochemical device is a device that converts chemical energy into electrical energy by an electrochemical reaction, and is a concept that includes a primary battery and a secondary battery. The secondary battery is capable of being charged and discharged, and is a concept that includes a lithium ion battery, a nickel-cadmium battery, a nickel-metal hydride battery, etc.
[0034] 1.Separation membrane In the present invention, a separator means a material that can provide a migration path for metal ions such as lithium ions between a positive electrode and a negative electrode while electrically insulating a negative electrode and a positive electrode to prevent a short circuit between the positive electrode and the negative electrode. FIG. 1(a) is a schematic cross-sectional view of a separator 10 according to an embodiment of the present invention. The separator 10 according to the present invention includes a porous polymer substrate 11 having a plurality of pores, and an organic / inorganic composite porous coating layer 12 disposed on at least one surface of the polymer substrate. In addition, an adhesive coating layer 13 is formed on the outermost surface of the separator. In a preferred embodiment, the separator includes a polymer substrate, an organic / inorganic composite porous coating layer formed on one surface of the polymer substrate, and an adhesive coating layer formed on the surface of the organic / inorganic composite porous coating layer disposed on one surface of the organic / inorganic composite porous coating layer, which is the surface opposite to the surface on which the polymer substrate is disposed. The organic / inorganic composite porous coating layer and the adhesive coating layer may be formed on one surface or both surfaces of the polymer substrate. Hereinafter, the separation membrane of the present invention will be described in detail for each component.
[0035] 1) Porous polymer substrate The polymer substrate is a porous polymer membrane having a plurality of pores formed therein, and functions as a porous ion-conducting barrier that allows ions to pass while blocking electrical contact between the negative and positive electrodes. The pores include open pores that are interconnected to each other, allowing gas or liquid to pass from one side of the substrate to the other side.
[0036] In one embodiment of the present invention, the polymer substrate includes a polymer material, and the polymer material may include a thermoplastic resin from the viewpoint of imparting a shutdown function to the separator. The shutdown function refers to a function of preventing thermal runaway of the battery by blocking the movement of ions by dissolving the polymer material included in the substrate and closing the pores of the polymer substrate when the battery temperature becomes high. In one embodiment of the present invention, the thermoplastic resin may include a polyolefin resin having a melting temperature (melting point) of less than 200°C. Examples of the polyolefin resin include polyethylene, polypropylene, polybutene, polypentene, etc., and may include one or a mixture of two or more of them. As a specific example, the polyolefin resin may include two or more selected from polyethylene, polypropylene, and polypentene. As another example, the polyolefin resin may be polyethylene and / or polypropylene.
[0037] In one embodiment of the present invention, the weight average molecular weight (Mw) of the polyolefin resin may be 300,000 to 1,500,000. When the molecular weight is within the above range, the polymer substrate has excellent mechanical properties and good film formability. When the molecular weight (Mw) is too high, there is a problem that film formation becomes difficult.
[0038] Meanwhile, in the present invention, the weight average molecular weight (Mw) can be measured by gel permeation chromatography (GPC, PL GPC220, Agilent Technologies), and the measurement conditions can be set as follows.
[0039] -Column: PL Olexis (Polymer Laboratories) -Solvent: TCB (Trichlorobenzene) -Flow rate: 1.0ml / min -Sample concentration: 1.0mg / ml -Injection volume: 200μl -Column temperature: 160°C -Detector: Agilent High Temperature RI detector -Standard: Polystyrene (corrected by a cubic function)
[0040] The method for measuring the weight average molecular weight can be applied to the measurement of the weight average molecular weight of the polyolefin resin as well as to the polymer materials mentioned in the specification of the present application.
[0041] In addition to the polyolefin resin, the resin may include one or more selected from the group consisting of polyethylene terephthalate, polybutylene terephthalate, polyacetal, polyamide, polycarbonate, polyimide, polyether ether ketone, polyether sulfone, polyphenylene oxide, polyphenylene sulfide, and polyethylene naphthalene.
[0042] In one embodiment of the present invention, the porous polymer substrate may include one or more nonwoven fabric sheets or one or more polymer films. Alternatively, the porous substrate may include one or more nonwoven fabrics and one or more polymer films. In one embodiment of the present invention, the polymer substrate may be a single layer. Alternatively, the porous substrate may have a laminated structure in which two or more layers of nonwoven fabrics and / or films are laminated. The polymer film may refer to a film formed into a sheet by melting / pressing a polymer resin.
[0043] In the present invention, the polymer-based material preferably has a thickness of 7 μm to 15 μm. If the thickness exceeds this range and is too thick, the Li-ion conduction path becomes longer, which may cause an increase in resistance and subsequently degrade the battery performance. On the other hand, if the thickness is too thin, the function of the conductive barrier may be reduced, which may increase the occurrence of short circuits.
[0044] Meanwhile, in one embodiment of the present invention, the thickness of the polymer base material or the like can be measured using a contact type thickness gauge, for example, Mitutoyo's VL-50S-B.
[0045] Meanwhile, in one embodiment of the present invention, the average diameter of the pores of the polymer-based material may be 40 nm or less, and preferably, for example, 30 nm or less. If the pore size is excessively large beyond the above range, when pressure is applied during the manufacture of the battery, such as during the lamination process, deformation of the shape before / after compression may be large, which is undesirable.
[0046] The average pore diameter can be calculated using an image processing software (such as SigmaScan Pro 5.0) using a scanning electron microscopy (SEM) image. Alternatively, a capillary flow porometer can be used to obtain an air permeability curve for a 1 / 2 dry sample and an air permeability curve for a wet sample, and the size corresponding to the intersection of these two curves can be determined as the average pore diameter.
[0047] Meanwhile, in one embodiment of the present invention, the polymer-based material may have an air permeability of 100 sec / 100 cc or less, for example, 60 to 85 sec / 100 cc. If the air permeability is too low, i.e., not within the above range, the mechanical properties of the separator substrate are poor. On the other hand, if the air permeability is too high, the path of lithium ions (Li-ions) may become long, which may result in a shortened battery life.
[0048] In the present invention, the permeability time means the time required for 100 ml of air to pass through a sample such as a polymeric substrate or a separation membrane with a size of 1 square inch under a certain air pressure, and may be expressed in units of seconds / 100 cc. Also, it may be used interchangeably with the permeation time, and is usually expressed as a Gurley value or the like. In one embodiment of the present invention, the permeability may be measured according to the standard regulations in this technical field. For example, the permeability may be measured using a well-known Gurley Densometer according to ASTM D726-58 or ASTM D726-94, and may be measured, for example, using air at a pressure of 0.304 (kPa) or 1.215 kN / m 2 of water pressure in one square inch (or 6.54 cm 2 ) sample in seconds. According to another embodiment, the air permeability can be expressed in seconds by measuring the time it takes for 100 ml of air to pass through a 1 inch square sample at room temperature under a constant pressure of 4.8 inches H2O according to the Gurley measurement method of the Japanese Industrial Standard (JIS-P8117). In one embodiment of the present invention, the air permeability can be measured, for example, using an Asahi Seiko EG01-55-1MR device according to the standard.
[0049] In addition, in the present invention, the polymer-based material has a full width at half maximum peak height (FWHM) of 8.0 nm or less in the pore diameter distribution according to a normal distribution (Gaussian distribution) measured through the pore size distribution. The full width at half maximum peak height may be defined as the difference in size between two points on the x-axis that is half the maximum value on the y-axis (the most frequent value among the pore sizes) in a normal distribution for a pore size distribution shown by classifying pores formed inside the polymer-based material according to their sizes. In the distribution, the x-axis represents the size (diameter) of the pores, and the y-axis represents the frequency of the number of pores corresponding to the pore size on the x-axis (e.g., the number of pores or the percentage of the number of pores). In the present invention, the unit of the x-axis may be expressed in nm or μm. FIG. 6 is related to the full width at half maximum (FWHM) according to the PSD (pore size distribution) distribution, and the full width at half maximum (FWHM) can be expressed as the difference between two points X2 and X1 on the x-axis that correspond to 1 / 2 (1 / 2T) of the y-axis mode (T). Referring to FIG. 6, the full width at half maximum (FWHM) can be expressed as the difference between two points X2 and X1 on the x-axis that correspond to 1 / 2 (1 / 2T) of the y-axis mode (T). The difference can be expressed as an absolute value. Meanwhile, the normal distribution can represent symmetric and asymmetric distributions based on the maximum value, and any distribution other than normal.
[0050] Meanwhile, in one embodiment of the present invention, the half-width can be determined from the distribution of the remaining pores excluding the pore with the largest diameter. Meanwhile, in the present invention, the shape of the pores can be circular, elliptical or amorphous, and the cross section can be a closed curve. The diameter of the pores means the longest distance between any two points in the closed curve. When the above range is satisfied, the polymer substrate has a small pore size and a high uniformity of the pore size. A polymer substrate having these characteristics can exhibit high dimensional stability and high dielectric breakdown voltage.
[0051] In one embodiment of the present invention, the polymer substrate may have a resistance of 0.6 ohms or less. If the resistance is too high, it is undesirable since it may deteriorate the life characteristics during repeated charging and discharging of the battery. As described herein, the polymer substrate of the present invention has a small pore size and a low porosity, but the half width is uniformly distributed to 8.0 nm or less as described above, so that the resistance can be maintained at a low level.
[0052] Meanwhile, in one embodiment of the present invention, the porosity of the polymer-based material may be 20vol% to 50vol%. If the porosity is too low, by-products may be generated due to the degradation of lithium ions (Li-ions) during charging / discharging, and may accumulate in the pores, shortening the life of the battery. On the other hand, if the porosity is too high, the mechanical properties of the separator may be reduced, making it difficult to ensure uniform mechanical properties over the entire surface of the separator.
[0053] The porosity means the ratio of the volume occupied by pores to the total volume, and is expressed as a unit of vol%. It can be used interchangeably with terms such as porosity and net density. In the present invention, the measurement of the porosity is not particularly limited, and a method known in the art can be applied. For example, it can be measured by a BET (Brunauer-Emmett-Teller) measurement method using nitrogen gas, a water intrusion porosimeter method, a capillary flow porometer, or a mercury penetration method. Alternatively, in one embodiment of the present invention, the true density of the porous substrate is calculated from the density (apparent density) of the obtained porous substrate, the composition ratio of the materials contained in the porous substrate, and the density of each component, and the porosity of the porous substrate can be calculated from the difference between the apparent density and the net density. For example, the porosity can be calculated according to the following [Equation 1].
[0054] [Formula 1] Porosity (vol%) = {1-(apparent density / true density)} x 100
[0055] On the other hand, in the above formula, the apparent density can be calculated from the following [Formula 2].
[0056] [Formula 2] Apparent density (g / cm 3 ) = {Weight of porous substrate [g] / (Thickness of porous substrate [cm] × Area of porous substrate [cm 2 ])}
[0057] In one embodiment of the present invention, the porous substrate can be manufactured by a method for manufacturing a polymer film, preferably a wet manufacturing method, for example, the wet manufacturing method includes the steps of (S1) preparing a mixture, (S2) extruding the mixture and forming an extruded sheet, (S3) stretching the extruded sheet, (S4) removing the pore-forming agent, and (S5) heat fixing the extruded sheet.
[0058] In the step (S1), the type of polymer resin is appropriately selected according to the final properties of the separator, and the selected polymer resin is mixed with a pore-forming agent. The polymer resin may be the same as that of the porous substrate. For example, the polymer resin may be a polyolefin-based polymer resin. Examples of the polyolefin-based polymer resin include one selected from polyethylene, for example, high density polyethylene, linear low density polyethylene, low density polyethylene or ultra-high molecular weight polyethylene, polypropylene, polybutylene, polypentene, etc., or a combination of two or more of them.
[0059] The pore former is a material dispersed in a polymer, which shows the heterogeneity of the substrate produced by extrusion, stretching, etc., and is subsequently removed from the substrate. Thus, the portion of the substrate where the pore former was located remains in the form of pores in the substrate. The pore former is preferably a material that is liquid during the extrusion process, but a material that maintains a solid state can also be used. The pore former can be an aliphatic hydrocarbon solvent such as liquid paraffin, paraffin oil, mineral oil, or paraffin wax; a vegetable oil such as soybean oil, sunflower oil, rapeseed oil, palm oil, coconut oil, corn oil, grapeseed oil, cottonseed oil, etc.; or a plasticizer such as dialkyl phthalate. In particular, the plasticizer may be di-2-ethylhexyl phthalate (DOP), di-butyl-phthalate (DBP), di-isononyl phthalate (DINP), di-isodecyl phthalate (DIDP), butyl benzyl phthalate (BBP), etc. Among these, liquid paraffin (LP, also called "liquid paraffin") is particularly preferred.
[0060] In addition, the content of the pore-forming agent in the preparation of the separator can be appropriately adjusted to realize a desired level of porosity. In consideration of improving the air permeability, it is preferable that the content of the pore-forming agent is high, but if it is contained in an excessive amount, it may have a negative effect on the strength of the final substrate. Therefore, the content of the pore-forming agent may be 1 wt% to 80 wt% based on 100 wt% of the total of the polymer resin and the pore-forming agent, and may be adjusted to 70 wt% or less, 60 wt% or less, or 50 wt% or less within the above range as necessary, or may be adjusted to 1 wt% or more, 20 wt% or more, or 40 wt% or more. Meanwhile, in a specific embodiment of the present invention, in order to realize a suitable porosity of the porous substrate, for example, to realize a porosity of about 45% or less, the pore-forming agent may be included in a range of 1 wt% to 60 wt% based on the total amount of the polymer resin and the pore-forming agent.
[0061] Next, the mixture prepared in the above step is extruded through an extruder to obtain an extruded sheet. The extruder is not particularly limited and may be an extruder commonly used in the art, for example, an extruder equipped with a T-die or a tubular die. The extrusion process may be carried out at a normal extrusion temperature, and is preferably carried out at a temperature 10°C to 100°C higher than the melting point of the polymer resin used. If the extrusion process is carried out excessively beyond the above range, the polymer resin may be thermally degraded, making film formation difficult and deteriorating the physical properties of the substrate produced, which is undesirable. An extruded sheet may be obtained by such an extrusion process.
[0062] The extruded sheet is then introduced into a stretching process. This stretching process is carried out using a stretching machine commonly used in the art. The stretching machine may be, but is not limited to, a sequential biaxial stretching machine. In this way, the mechanical strength of the porous substrate can be increased by stretching the extruded sheet. The stretching process is carried out in a machine direction (MD, machine direction, lengthwise direction) and / or a transverse direction (TD, vertical direction). The stretching process in all or one of these directions increases the tensile strength in the corresponding stretching direction. If necessary, the separation membrane of the present invention may be stretched in the machine direction (MD) and / or transverse direction (TD) alone (e.g., uniaxial stretching), simultaneously or sequentially (e.g., biaxial stretching) in the stretching process. Meanwhile, in one embodiment of the present invention, the temperature of the membrane may be controlled to 100°C to 130°C, preferably 110°C to 125°C. For example, the temperature of the membrane during the stretching can be controlled in the range of 115° C. to 121° C. When the stretching step is carried out within the above temperature range, a uniform membrane with small pores can be obtained.
[0063] Next, the pore-forming agent is removed from the extruded sheet obtained above. The pore-forming agent is removed by extraction using a solvent and drying. Also, as a result of this removal, the spaces occupied by the pore-forming agent are formed as pores. Any solvent capable of extracting the pore-forming agent can be used as the solvent for extracting the pore-forming agent, but preferably, methyl ethyl ketone, methylene chloride, hexane, etc., which have high extraction efficiency and quick drying, are suitable. Preferably, the solvent is methylene chloride, for example, methylene dichloride (MC). As the extraction method, any common solvent extraction method such as an immersion method, a solvent spray method, an ultrasonic method, etc., can be used individually or in combination. After the extraction of the pore-forming agent, the substrate is heat-set, thereby finally obtaining a separator having the desired physical properties, porosity, and air permeability. The heat-set step can be performed using a heating device, such as an oven, capable of applying an appropriate temperature required for heat-set. In particular, the first dried membrane is heat-set to reduce the shrinkage rate of the final membrane by removing residual stress. Heat-set is a method of fixing a membrane and applying heat to forcibly hold a membrane that is about to shrink, thereby removing residual stress. A higher heat-set temperature is advantageous for reducing the shrinkage rate, but if the temperature is too high, the membrane will partially melt, causing the formed pores to be blocked, resulting in reduced permeability. The preferred heat-set temperature is selected within a temperature range in which about 10 wt% to 30 wt% of the crystalline portion of the membrane will melt. If the heat setting temperature is selected to be lower than the temperature at which about 10 wt % of the crystalline portion of the film melts, the reorientation of the polyethylene molecules in the film is insufficient, and therefore there is no effect of removing residual stress in the film. If the heat setting temperature is selected to be higher than the temperature at which about 30 wt % of the crystalline portion of the film melts, the pores are blocked due to partial melting, and the permeability decreases.
[0064] 2) Organic / inorganic composite porous coating layer In the present invention, the separation membrane includes an organic / inorganic composite porous coating layer formed on at least one surface of a polymer-based material. The organic / inorganic composite porous coating layer is composed of a binder resin and inorganic particles, and has a structure in which a large number of micropores are included therein and these micropores are connected to each other, so that the separation membrane can be a porous layer through which gas or liquid can pass from one side to the other side.
[0065] In a specific embodiment of the present invention, the organic / inorganic composite porous coating layer includes inorganic particles and a binder resin, and is formed on the surface of the polymer substrate. The organic / inorganic composite porous coating layer may be formed by dispersing a water-dispersible binder resin in an aqueous solvent such as water to form an aqueous slurry, which is then coated and dried. As a result, the binder resin is introduced in the organic / inorganic composite porous coating layer in the form of particles having a predetermined diameter. That is, the organic / inorganic composite porous coating layer may be a mixed phase of inorganic particles and particulate organic binder resin. As the binder resin is introduced in the form of particles into the organic / inorganic composite porous coating layer as described above, the organic / inorganic composite porous coating layer is sufficiently porous to have excellent ion permeability, and the binder resin does not flow into the polymer substrate, so that the air permeability and resistance properties of the polymer substrate are not reduced.
[0066] The organic / inorganic composite porous coating layer includes a binder resin and inorganic particles. The inorganic particles and the binder resin may be contained in a weight ratio of 75:25 to 90:10, and the mixture of the inorganic particles and the binder resin may be 99 wt% or more in the entire organic / inorganic composite porous coating layer.
[0067] In one embodiment of the present invention, the average pore size of the organic / inorganic composite porous coating layer may be 10 nm to 900 nm, preferably 20 nm to 100 nm. Meanwhile, the porosity of the organic / inorganic composite porous coating layer is preferably 50% to 85%. When the porosity is 85% or less, the mechanical properties that allow the coating layer to maintain its shape during the pressing process for bonding it to the electrode can be ensured, and the surface opening ratio is not too high, so that it is suitable for ensuring adhesive strength. In addition, when the porosity is 50% or more, it is advantageous from the viewpoint of ion permeability, since it is higher than the porosity of most polymer substrates.
[0068] In one embodiment of the present invention, the thickness of the organic / inorganic composite porous coating layer on one side of the polymer substrate can be 0.1 μm to 10 μm, for example, 0.5 μm to 6 μm, or 1 μm to 5 μm. From the viewpoint of increasing the adhesive strength and strength with the electrode within the above numerical range, it is preferable to set the thickness to 1 μm or more. On the other hand, if the thickness is 10 μm or less, it is advantageous from the viewpoint of the cycle characteristics and resistance characteristics of the battery.
[0069] a. Inorganic particles In a specific embodiment of the present invention, the inorganic particles are not particularly limited as long as they are electrochemically stable within the range of the battery driving voltage. That is, the inorganic particles that can be used in the present invention are those that are electrochemically stable within the operating voltage range of the applied electrochemical element (for example, Li / Li + There are no particular limitations as long as oxidation and / or reduction reactions do not occur at a potential of 0 to 5 V relative to the reference potential. In particular, when inorganic particles having a high dielectric constant are used as the inorganic particles, the degree of dissociation of an electrolyte salt, for example, a lithium salt, in the liquid electrolyte can be increased, thereby improving the ionic conductivity of the electrolyte.
[0070] For the reasons described above, it is preferable that the inorganic particles include inorganic particles having a high dielectric constant, with a dielectric constant of 5 or more, preferably 10 or more. Non-limiting examples of inorganic particles having a dielectric constant of 5 or more include BaTiO3, Pb(Zr,Ti)O3 (PZT), b 1-x La x Zr 1-y Ti y O3(PLZT, 0 <x<1、0<y<1)、Pb(Mg 1 / 3 Nb 2 / 3 )O3-PbTiO3 (PMN-PT), hafnia (HfO2), SrTiO3, SnO2, CeO2, MgO, Mg(OH)2, NiO, CaO, ZnO, ZrO2, SiO2, Y2O3, Al2O3, AlOOH, Al(OH)3, SiC and TiO2, or mixtures thereof.
[0071] In addition, as the inorganic particles, inorganic particles having lithium ion transfer ability, that is, inorganic particles that contain lithium element but have the function of moving lithium ions without storing lithium can be used. Non-limiting examples of the inorganic particles having lithium ion transfer ability include lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0 < x < 2, 0 < y < 3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y -based glasses such as 14Li2O - 9Al2O3 - 38TiO2 - 39P2O5 (0 < x < 4, 0 < y < 13), lithium lanthanum titanate (Li x La y TiO3, 0 < x < 2, 0 < y < 3), Li 3.25 Ge 0.25 P 0.75 S4 and other lithium germanium thiophosphates (Li x Ge y P z S w , 0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), lithium nitride such as Li3N (Li x N y , 0 < x < 4, 0 < y < 2), SiS2-based glasses such as Li3PO4 - Li2S - SiS2 (Li x Si y S z , 0 < x < 3, 0 < y < 2, 0 < z < 4), P2S5-based glasses such as LiI - Li2S - P2S5 (Li x P y S z , 0 < x < 3, 0 < y < 3, 0 < z < 7), or mixtures thereof, and the like.
[0072] In addition, the average particle size (D 50) is not particularly limited, but is preferably in the range of 0.1 μm to 2.5 μm in order to form a coating layer of uniform thickness and ensure appropriate porosity. If it is less than 0.1 μm, dispersibility may decrease due to a high specific surface area, and if it exceeds 2.5 μm, the thickness of the coating layer formed may increase.
[0073] B. Binder resin In the present invention, the organic / inorganic composite porous coating layer includes a binder resin, which may include 90 wt% or more of particulate binder resin relative to 100 wt% of the binder resin. The particulate binder resin has adhesive properties, and accumulates the binder resin and the inorganic particles in a layer structure on the surface of the polymer substrate by adhesion between particles or adhesion between the binder particles and the inorganic particles. In addition, the particulate binder resin may include a water-dispersible binder resin that is dispersed without dissolving in water or an aqueous solvent containing water.
[0074] The particulate binder resin is a material that can change to a gel or liquid state while heat and / or pressure are applied, and can return to a solid state after the heat and pressure are removed, and is electrochemically stable. In a specific embodiment of the present invention, the particulate binder resin may have a glass transition temperature (Tg) in the range of about -100°C to about 50°C, and a melting temperature (Tm) in the range of about 50°C to about 150°C. When the Tg of the particulate binder resin satisfies the above range, it is advantageous in achieving a predetermined adhesive strength, and when the Tg exceeds the above range, especially when the Tg is above room temperature, the ion conductivity may decrease. In one embodiment of the present invention, the Tg can be measured by a thermogravimetric analysis method using a TA instrument.
[0075] According to a specific embodiment of the present invention, the particulate binder resin includes a polyvinylidene fluoride-based polymer (PVdF-based polymer) (first binder polymer) and a (meth)acrylic polymer (second binder polymer). The first binder polymer (PVdF-based) and the second binder polymer (acrylic-based) may be preferably included in a ratio of 40:60 to 5:95 based on a weight ratio. For example, the first binder polymer (PVdF-based) and the second binder polymer (acrylic-based) may be included in a ratio of 30:70 to 5:95. If the content of the first binder polymer is excessively high, the adhesive strength may be improved, but the resistance of the separator may be excessively increased due to over-adhesion during the lamination process. On the other hand, if the content of the first binder polymer is less than the above range, it is difficult to ensure a desired level of adhesive strength.
[0076] In the present specification, the PVdF-based polymer may include a homopolymer of vinylidene fluoride monomer; a copolymer (PVdF-based copolymer) including vinylidene fluoride and another monomer (comonomer) copolymerizable with vinylidene fluoride; or both. According to a specific embodiment of the present invention, the particulate polymer may include a copolymer resin in consideration of the adhesive strength of the electrode adhesive layer. Also, the PVdF copolymer may be a copolymer in which vinylidene fluoride and a comonomer are copolymerized in a ratio of 60:40 to 96:4 based on parts by weight. For example, within the above range, the vinylidene fluoride and the comonomer may be copolymerized in a ratio of 80:20 to 96:4 or 90:10 to 97:3 based on parts by weight. That is, in the present invention, the PVdF copolymer may have a degree of substitution by the comonomer appropriately adjusted within a range of 1 wt% to 40 wt%. In one embodiment of the present invention, the degree of substitution may be in the range of 1 wt% to 10 wt%.
[0077] In the present invention, the degree of substitution of the comonomer can be measured based on the integral value of the characteristic peak of the monomer confirmed by 1H NMR (Nuclear Magnetic Resonance) spectrum. For the analysis of the degree of substitution, refer to Journal of Materials Chemistry, 2012, 22, 341 or AMT-3412-0k. The NMR spectrum can be confirmed using a suitable device such as Bruker Avance III HD 700MHz NMR or Varian 500MHz NMR.
[0078] The comonomer may be a fluorinated monomer or a chlorine-based monomer, and is preferably a fluorinated monomer. Non-limiting examples of the fluorinated monomer include at least one selected from the group consisting of vinyl fluoride, trifluoroethylene (VF3), chlorofluoroethylene (CTFE), 1,2-difluoroethylene, tetrafluoroethylene (TFE), hexafluoropropylene (HFP), perfluoro(alkyl vinyl) ethers such as perfluoro(methyl vinyl) ether (PMVE), perfluoro(ethyl vinyl) ether (PEVE) and perfluoro(propyl vinyl) ether (PPVE), perfluoro(1,3-dioxole), and perfluoro(2,2-dimethyl-1,3-dioxole) (PDD), and according to a specific embodiment of the present invention, the comonomer includes hexafluoropropylene.
[0079] In the present invention, the weight average molecular weight (Mw) of the PVdF polymer in the particulate binder resin is not particularly limited, but is preferably from 10,000 to 500,000, and more preferably from 50,000 to 500,000.
[0080] According to a specific embodiment of the present invention, the particulate binder resin may contain a (meth)acrylic polymer. According to a specific embodiment of the present invention, the (meth)acrylic polymer contains a (meth)acrylic acid ester as a monomer, and non-limiting examples thereof include (meth)acrylic polymers containing butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, ethyl (meth)acrylate, methyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, n-oxyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, lauryl (meth)acrylate, and tetradecyl (meth)acrylate as monomers. The (meth)acrylic polymer may be contained in an amount of 30% by weight or less relative to 100% by weight of the particulate binder resin.
[0081] On the other hand, in one specific embodiment of the present invention, the particulate binder resin may have a particle size of 100 nm to 1 μm, 100 nm to 500 nm, or 200 nm to 500 nm, or 200 nm to 350 nm, or 200 nm to 300 nm.
[0082] In the present invention, the method for producing the particulate binder resin is not particularly limited, and a method for producing a general particulate polymer, such as a solution polymerization method, a suspension polymerization method, or an emulsion polymerization method, can be applied. Among them, the emulsion polymerization method and the suspension polymerization method are preferred because they can be polymerized in water and can be used as a slurry for forming an organic / inorganic composite porous coating layer as it is.
[0083] c. Other additives In a specific embodiment of the present invention, the organic / inorganic composite porous coating layer may further contain additives as necessary. These additives include, for example, thickeners. The organic / inorganic composite porous coating layer may further improve the coating properties of the slurry described below and the charge / discharge characteristics of the resulting electrochemical device by containing a dispersant or a thickener.
[0084] Examples of the thickener include cellulose compounds such as carboxymethylcellulose, methylcellulose, and hydroxypropylcellulose; ammonium salts or alkali metal salts of the cellulose compounds; polycarboxylic acids such as poly(meth)acrylic acid and modified poly(meth)acrylic acid; alkali metal salts of the polycarboxylic acids; polyvinyl alcohol (co)polymers such as polyvinyl alcohol, modified polyvinyl alcohol, and ethylene-vinyl alcohol copolymers; water-soluble polymers such as saponified copolymers of unsaturated carboxylic acids such as (meth)acrylic acid, maleic acid, and fumaric acid and vinyl esters. Particularly preferred thickeners among these include alkali metal salts of carboxymethylcellulose and alkali metal salts of poly(meth)acrylic acid.
[0085] In one embodiment of the present invention, when the organic / inorganic composite porous coating layer contains a thickener, the usage ratio of the thickener is preferably 5 wt% or less relative to 100 wt% of the entire organic / inorganic composite porous coating layer, and more preferably 0.1 mass% to 3 mass%.
[0086] Examples of the dispersing agent include acrylic copolymers, cyanoethyl polyvinyl alcohol, baicalin, luteolin, taxifolin, myricetin, quercetin, rutin, catechin, epigallocatechin gallate, butein, piceatannol, phenolic compounds including tannic acid, pyrogallol, amylose, amylopectin, xanthan gum, fatty acid compounds, and polymer compounds of two or more of these.
[0087] In one embodiment of the present invention, when the organic / inorganic composite porous coating layer contains a dispersant, the usage ratio of the dispersant is preferably 5 wt% or less relative to 100 wt% of the entire organic / inorganic composite porous coating layer, and more preferably 0.1 mass% to 3 mass%.
[0088] d. Manufacturing method of organic / inorganic composite porous coating layer In the present invention, the organic / inorganic composite porous coating layer is formed by dispersing inorganic particles and a particulate binder resin in an appropriate aqueous solvent as a dispersion medium to prepare a slurry for forming the organic / inorganic composite porous coating layer, and applying the slurry onto the surface of the polymer substrate and drying the slurry.
[0089] The slurry may be prepared by mixing inorganic particles and a particulate binder resin with an aqueous solvent, or may be a result of a polymer emulsion obtained by suspension polymerization, liquid phase polymerization, emulsion polymerization, etc. The aqueous solvent is preferably an aqueous medium containing water. By using an aqueous medium, the slurry has a low adverse effect on the environment, is highly stable for workers who handle it, and can realize a thin organic / inorganic composite porous coating layer.
[0090] Meanwhile, in one embodiment of the present invention, the slurry may be adjusted to have a solid content of 30 wt% or less. If the solid content of the slurry exceeds 30 wt%, the viscosity of the slurry becomes too high, making it difficult to control the thickness when coating the slurry. On the other hand, if the solid content of the slurry is too low, uncoated areas may occur, and the surface of the polymer substrate may be exposed without being covered with the slurry, causing a short circuit.
[0091] The method of applying the slurry may be a doctor blade coating method, a bar coating method, a dip coating method, a reverse roll coating method, a direct roll coating method, a gravure coating method, an extrusion coating method, a brush coating method, or the like. From the viewpoint of being able to control the thickness uniformly, a bar coating method, a doctor blade coating method, a gravure coating method, or the like is preferred.
[0092] The method for drying the slurry is not particularly limited, and examples of the method that can be used include drying with warm air, hot air, low-humidity air, vacuum drying, and drying by irradiation with (far) infrared rays or electron beams.
[0093] In the present invention, the organic / inorganic composite porous coating layer has a structure in which polymer particles are dispersed between the separator and the electrode, and thus does not impede ion conduction between the electrode and the separator, resulting in a low resistance increase rate and excellent life characteristics.
[0094] 3) Adhesive coating layer The adhesive coating layer is formed on the surface of the organic / inorganic composite porous coating layer, which is the opposite side to the surface on which the polymer substrate is disposed, and includes a polyvinylidene fluoride (PVdF) binder resin. The adhesive coating layer may preferably include 90 wt% or more of the PVdF binder resin relative to 100 wt% of the total. For example, the adhesive coating layer may include 90 wt% or more, 95 wt% or more, or 99 wt% or more of the PVdF binder resin relative to 100 wt% of the total. Alternatively, the binder resin may be entirely a PVdF binder resin.
[0095] In the present invention, the binder resin may contain 90 wt% or more of particulate binder resin relative to 100 wt% of the binder resin. The particulate binder resin has adhesive properties, and accumulates the binder resin in a layer structure on the surface of the organic / inorganic composite porous coating layer by adhesion between particles. That is, in the present invention, the adhesive coating layer contains a particulate PVdF-based binder resin, and for example, the binder resin in the adhesive coating layer may include a particulate PVdF-based binder resin.
[0096] In one embodiment of the present invention, the PVdF-based binder resin of the adhesive coating layer preferably has a weight-average molecular weight of 600,000 or less, 400,000 or less, or 300,000 or less. When the weight-average molecular weight is 600,000 or less, it is advantageous for improving the adhesive strength by increasing the flexibility. However, when the weight-average molecular weight is less than 50,000, it may dissolve in the electrolyte solution, increasing the viscosity of the electrolyte solution, which may result in a decrease in ion conductivity, so that the PVdF-based binder resin may have a weight-average molecular weight of 50,000 or more. Here, the weight-average molecular weight of the PVdF-based binder resin can be determined by gel permeation chromatography (GPC method). The PVdF-based binder resin having a relatively low molecular weight as described above can be obtained preferably by emulsion polymerization or suspension polymerization, particularly preferably by suspension polymerization.
[0097] In the present invention, the PVdF-based binder resin may include a homopolymer of vinylidene fluoride (i.e., polyvinylidene fluoride), a copolymer of vinylidene fluoride and other copolymerizable monomers, or a mixture thereof. The monomer copolymerizable with vinylidene fluoride may include, for example, one or more selected from tetrafluoroethylene, hexafluoropropylene, trifluoroethylene, chlorofluoroethylene, 1,2-difluoroethylene, perfluoro(methyl vinyl) ether, perfluoro(ethyl vinyl) ether, perfluoro(propyl vinyl) ether, perfluoro(1,3 dioxole), perfluoro(2,2-dimethyl-1,3-dioxole), trichloroethylene, and vinyl fluoride. In one embodiment of the present invention, the PVdF-based binder resin has a melting temperature (Tm) of 150° C. or less, preferably a Tm of 140° C. or less, from the viewpoint of adhesive strength during heat adhesion. For this purpose, the binder resin includes, as a polymerization unit, a copolymer of vinylidene fluoride and a monomer copolymerizable with vinylidene fluoride, and the copolymer may contain 70 wt% or more of vinylidene fluoride. Also, the copolymer may have a substitution degree with the other copolymerizable monomers as described above of 10 wt% to 40 wt%, for example, 1 wt% to 10 wt%.
[0098] Meanwhile, in one embodiment of the present invention, the adhesive coating layer may be formed to a thickness of 8% to 30% of the thickness of the organic / inorganic composite porous coating layer (first coating layer).
[0099] The adhesive coating layer can be formed, for example, by the following method, but is not limited thereto.
[0100] In the present invention, the adhesive coating layer is formed by dispersing a particulate binder resin in a suitable aqueous solvent as a dispersion medium to prepare a composition for forming the adhesive coating layer, applying the composition onto the surface of the organic / inorganic composite porous coating layer, and drying the composition. The composition may be prepared by mixing a particulate binder resin with an aqueous solvent, or may be a polymer emulsion obtained by suspension polymerization, liquid phase polymerization, emulsion polymerization, etc. The aqueous solvent is preferably an aqueous medium containing water. By using an aqueous medium, the slurry has a low adverse effect on the environment, is highly stable for workers who handle it, and can achieve a thin adhesive coating layer.
[0101] The composition can be applied by a method such as a bar coating method, a doctor blade coating method, a dip coating method, a reverse roll coating method, a direct roll coating method, a gravure coating method, an extrusion coating method, or a brush coating method. From the viewpoint of being able to control the thickness uniformly, the bar coating method, the doctor blade coating method, and the gravure coating method are preferred.
[0102] The method for drying the composition is not particularly limited, and examples of the method that can be used include drying with wind such as warm air, hot air, or low-humidity air, vacuum drying, and drying by irradiation with (far) infrared rays or electron beams.
[0103] In the present invention, the adhesive coating layer has a structure in which polymer particles are dispersed between the separator and the electrode, and does not interfere with ion conduction between the electrode and the separator, resulting in a low resistance increase rate and excellent life characteristics.
[0104] Meanwhile, the separator according to the present invention having the above-mentioned structural characteristics may have a resistance of 0.6 ohms or less. In addition, the separator may have an air permeability of 100 sec / 100 cc or less. If the resistance and / or air permeability of the separator is excessively high, it is not preferable since it may deteriorate the life characteristics during repeated charging and discharging of the battery. Since the composite coating layer and the adhesive coating layer of the separator according to the present invention are prepared in an aqueous manner, the separator may have a resistance of 0.6 ohms or less and, together with or independently, a low air permeability of 100 sec / 100 cc or less even when the composite coating layer and the adhesive coating layer are disposed on the surface of the polymer substrate.
[0105] In the present invention, the resistance is a value when the separator is immersed in an electrolyte. In one embodiment of the present invention, the resistance may be a value measured by an alternating current method (frequency 10,000 to 100,000 Hz) at 25° C. after immersing the polymer-based material in the electrolyte. The electrolyte may be a mixture of ethylene carbonate and ethyl methyl carbonate in a volume ratio of 3:7 as a solvent, further containing vinylene carbonate at a ratio of 2 wt % with respect to the total solvent, and containing LiPF6 at a concentration of 1 M.
[0106] 2. An electrode assembly including the separator Meanwhile, the present invention provides a secondary battery including the separator, the battery including a negative electrode, a positive electrode, and a separator interposed between the negative electrode and the positive electrode, the separator being a low resistance separator having the above-mentioned characteristics.
[0107] In the present invention, the positive electrode comprises a positive electrode current collector and a positive electrode active material layer on at least one surface of the current collector, the positive electrode active material layer including a positive electrode active material, a conductive material, and a binder resin. The positive electrode active material may be a layered compound such as lithium manganese composite oxide (LiMn2O4, LiMnO2, etc.), lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; 1+x Mn 2-x O4 (where x is 0 to 0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiFe3O4, V2O5, and Cu2V2O7; and the chemical formula LiNi 1-x M x Lithium nickel oxide with Ni site represented by the formula LiMnO2 (where M=Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x is 0.01 to 0.3); 2-x M xLithium manganese composite oxides represented by O2 (where M is Co, Ni, Fe, Cr, Zn or Ta, and x is from 0.01 to 0.1) or Li2Mn3MO8 (where M is Fe, Co, Ni, Cu or Zn); LiMn2O4 in which part of Li in the chemical formula is substituted by alkaline earth metal ions; disulfide compounds; It can contain one or a mixture of two or more of Fe2(MoO4)3.
[0108] In the present invention, the negative electrode includes a negative electrode current collector and a negative electrode active material layer containing a negative electrode active material, a conductive material, and a binder resin on at least one surface of the current collector. As the negative electrode active material, the negative electrode includes carbon such as lithium metal oxide, graphitizable carbon, and graphite-based carbon; Li x Fe2O3 (0 ≤ x ≤ 1), Li x WO2 (0 ≤ x ≤ 1), Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, Group 1, Group 2, Group 3 elements of the periodic table, halogen; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8) and other metal composite oxides; lithium metal; lithium alloy; silicon-based alloy; tin-based alloy; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, and Bi2O5; conductive polymers such as polyacetylene; Li-Co-Ni-based materials; It can contain one or a mixture of two or more selected from titanium oxides.
[0109] In a specific embodiment of the present invention, the conductive material may be, for example, any one selected from the group consisting of graphite, carbon black, carbon or metal fiber, metal powder, conductive whisker, conductive metal oxide, activated carbon, and polyphenylene derivatives, or a mixture of two or more conductive materials thereof. More specifically, the conductive material may be any one selected from the group consisting of natural graphite, artificial graphite, super-p, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, denka black, aluminum powder, nickel powder, zinc oxide, potassium titanate, and titanium oxide, or a mixture of two or more conductive materials thereof.
[0110] The current collector is not particularly limited as long as it has high conductivity without inducing a chemical change in the battery. For example, stainless steel, copper, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel whose surface has been treated with carbon, nickel, titanium, silver, or the like can be used.
[0111] The binder resin may be a polymer commonly used in electrodes in the art. Non-limiting examples of such binder resins include polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethylmethacrylate, polyethylhexyl acrylate, polybutylacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinylacetate, ethylene-vinyl acetate copolymer, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, and cellulose acetate propionate. Examples of suitable cellulose acetate copolymers include, but are not limited to, cyanoethyl acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, and carboxyl methyl cellulose.
[0112] The electrode assembly prepared as above can be placed in a suitable case and an electrolyte can be injected to manufacture a battery.
[0113] In the present invention, the electrolyte is A+ B - A salt having the structure: + Li + , Na + , K + or a combination thereof, - PF6 - , BF4 - , Cl - , Br - , I - , ClO4 - , AsF6 - , CH3CO2 - , CF3SO3 - , N(CF3SO2)2 - , C(CF2SO2)3 - or a combination thereof, dissolved or dissociated in an organic solvent such as, but not limited to, propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), gamma butyrolactone (g-butyrolactone), or a mixture thereof.
[0114] The present invention also provides a battery module including a battery having the electrode assembly as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source. Specific examples of the device include, but are not limited to, a power tool powered by a battery-type motor, electric vehicles including electric vehicles (EV), hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), etc., electric two-wheeled vehicles including electric bicycles (E-bikes) and electric scooters (E-scooters), electric golf carts, and power storage systems.
[0115] Hereinafter, the present invention will be described in detail with reference to examples in order to specifically explain the present invention. However, the examples of the present invention can be modified in various different forms, and the scope of the present invention should not be construed as being limited to the examples detailed below. The examples of the present invention are provided to more completely explain the present invention to those having average knowledge in the art.
[0116] [Example] In Examples 1 and 2, a polymer substrate made of polypropylene having a thickness and porosity as shown in Table 1 below was prepared.
[0117] [Table 1]
[0118] Example 1 PVdF-HFP (Arkema, particle size 0.2 μm, HFP substitution degree about 5 wt%) was added and dispersed in an acrylic water-dispersed emulsion (Toyo Ink, CSB130, solid content 40%, particle size 177 nm). The acrylic and PVdF were mixed so that the content ratio by weight was 80:10. Next, Al2O3 (Nippon Light Metal Co., Ltd., LS235, particle size 510 nm) was added and dispersed. In addition, carboxyl methyl cellulose (Delchem, SG-L02) was added as a thickener and dispersed to prepare a slurry for forming an organic / inorganic composite porous coating layer. The solid content of the slurry was 30 wt%, and the content ratio of the binder resin (acrylic binder particles and PVdF particles) to the inorganic particles was 15:85 by weight. The slurry was mixed for 2 hours using a basket milling device, and then coated on one side of a polymer substrate using a doctor blade and dried to form an organic / inorganic composite porous coating layer.
[0119] PVdF-HFP (Arkema, particle size 0.2 μm, HFP substitution degree about 5 wt%) was added and dispersed in deionized water to prepare a composition for forming an adhesive coating layer. The solid content of the composition was 20 wt%. The composition was applied to one side of the organic / inorganic composite porous coating layer using a doctor blade and dried to form an adhesive coating layer.
[0120] In the separation membrane obtained in Example 1, the total thickness (one side) of the organic / inorganic composite porous coating layer and the adhesive coating layer was 4.1 μm, and the thickness ratio of the organic / inorganic composite porous coating layer to the adhesive coating layer was about 7: 1. FIG. 1(b) is a schematic diagram of Example 1.
[0121] Example 2 A separation membrane was prepared in the same manner as in Example 1, except that the total thickness (one side) of the organic / inorganic composite porous coating layer and the adhesive coating layer was 4.2 μm. In the separation membrane of Example 2, the thickness ratio of the organic / inorganic composite porous coating layer to the adhesive coating layer was about 7:1.
[0122] [Comparative Example] Comparative Example 1 A polymer substrate made of polypropylene having the thickness and porosity shown in Table 2 below was prepared.
[0123] [Table 2]
[0124] PVdF-HFP (Arkema, particle size 0.2 μm, HFP substitution degree about 5 wt%) was added and dispersed in an acrylic water-dispersed emulsion (Toyo Ink, CSB130, solid content 40%, particle size 177 nm). The acrylic and PVdF were mixed so that the content ratio by weight was 80:20. Next, Al2O3 (Nippon Light Metal Co., Ltd., LS235, particle size 510 nm) was added and dispersed. In addition, carboxyl methyl cellulose (Delchem, SG-L02) was added as a thickener and dispersed to prepare a slurry for forming an organic / inorganic composite porous coating layer. The solid content of the slurry was 30 wt%, and the content ratio of the binder resin (acrylic binder particles and PVdF particles) to the inorganic particles was 15:85 by weight. The slurry was mixed for 2 hours using a basket milling device. The slurry was applied to one side of a polymer substrate using a doctor blade and dried to form an organic / inorganic composite porous coating layer. In the separation membrane obtained in Comparative Example 1, the thickness (one side) of the organic / inorganic composite porous coating layer was 4.1 μm. FIG. 2 is a schematic diagram showing the cross-sectional structure of the separation membrane of Comparative Example 1.
[0125] Comparative Example 2 A polymer substrate made of polypropylene having a thickness and porosity as shown in Table 2 was prepared. PVdF-HFP (Arkema, particle size 0.2 μm, HFP substitution degree about 5 wt%) was added and dispersed in an acrylic water dispersion emulsion (Toyo Ink, CSB130, solid content 40%, particle size 177 nm). The acrylic and PVdF were mixed so that the content ratio by weight was 80:10. Next, Al2O3 (Nippon Light Metal Co., Ltd., LS235, particle size 510 nm) was added and dispersed. In addition, carboxymethylcellulose (Delchem, SG-L02) was added as a thickener and dispersed to prepare a slurry for forming an organic / inorganic composite porous coating layer. The solid content of the slurry was 30 wt%, and the content ratio of the binder resin (acrylic binder particles and PVdF particles) to the inorganic particles was 15:85 by weight. The slurry was mixed for 2 hours using a basket milling device, and then coated onto one side of a polymer substrate using a doctor blade and dried to form an organic / inorganic composite porous coating layer.
[0126] PVdF-HFP (Arkema, particle size 0.2 μm, HFP substitution degree about 5 wt%) was added and dispersed in deionized water to prepare a composition for forming an adhesive coating layer. The solid content of the composition was 20 wt%. The composition was applied to one side of the organic / inorganic composite porous coating layer using a doctor blade and dried to form an adhesive coating layer.
[0127] In the separation membrane obtained in Comparative Example 2, the total thickness of the organic / inorganic composite porous coating layer and the adhesive coating layer was 4.2 μm. In addition, the thickness ratio of the organic / inorganic composite porous coating layer to the adhesive coating layer was about 7:1. Figure 3 is a schematic diagram showing the cross-sectional structure of the separation membrane of Comparative Example 2.
[0128] Comparative Example 3 A polymer substrate made of polypropylene having the thickness and porosity shown in Table 2 above was prepared.
[0129] PVdF-HFP (Arkema, particle size 0.2 μm, HFP substitution degree about 5 wt%) was added and dispersed in an acrylic water-dispersed emulsion (Toyo Ink, CSB130, solid content 40%, particle size 177 nm). The acrylic and PVdF were mixed so that the content ratio by weight was 80:20. Next, Al2O3 (Nippon Light Metal Co., Ltd., LS235, particle size 510 nm) was added and dispersed. In addition, carboxyl methyl cellulose (Delchem, SG-L02) was added as a thickener and dispersed to prepare a slurry for forming an organic / inorganic composite porous coating layer. The solid content of the slurry was 30 wt%, and the content ratio of the binder resin (acrylic binder particles and PVdF particles) to the inorganic particles was 15:85 by weight. The slurry was mixed for 2 hours using a basket milling device. The slurry was applied to one side of a polymer substrate using a doctor blade and dried to form an organic / inorganic composite porous coating layer. In the separation membrane obtained in Comparative Example 3, the thickness (one side) of the organic / inorganic composite porous coating layer was 4.1 μm. FIG. 4 is a schematic diagram showing the cross-sectional structure of the separation membrane of Comparative Example 3.
[0130] Comparative Example 4 PVdF-HFP (Arkema, particle size 0.2 μm, HFP substitution degree about 5 wt%) as a binder resin was dissolved in acetone as a solvent, and then Al2O3 (Nippon Light Metal Co., Ltd., LS235, particle size 510 nm) was added and dispersed. Carboxymethylcellulose (Delchem, SG-L02) as a thickener was added and dispersed to prepare a slurry for forming an organic / inorganic composite porous coating layer. The solid content of the slurry was 30 wt%, and the content ratio of the binder resin to the inorganic particles was 15:85 by weight. The slurry was mixed for 2 hours using a basket milling device. The slurry was applied to one side of a polymer substrate using a doctor blade and dried to form an organic / inorganic composite porous coating layer.
[0131] PVdF-HFP (Arkema, particle size 0.2 μm, HFP substitution degree about 5 wt%) was added and dispersed in deionized water to prepare a composition for forming an adhesive coating layer. The solid content of the composition was 20 wt%. The composition was applied to one side of the organic / inorganic composite porous coating layer using a doctor blade and dried to form an adhesive coating layer.
[0132] In the separation membrane obtained in Comparative Example 4, the total thickness (one side) of the organic / inorganic composite porous coating layer and the adhesive coating layer was 4.1 μm, and the thickness ratio of the organic / inorganic composite porous coating layer to the adhesive coating layer was about 7: 1. FIG 5 is a schematic diagram showing the cross-sectional structure of the separation membrane of Comparative Example 4.
[0133] [Physical property measurements] The thickness, air permeability, and resistance (ER) of the separation membrane obtained in each Example and Comparative Example were measured before and after compression. In addition, a pressure of 5.2 MPa was applied to the separation membrane of each Example and Comparative Example for 10 seconds at 70°C, and then the physical properties were measured. [Table 3] shows the physical properties of the separation membrane before compression, and [Table 4] shows the physical properties of the separation membrane after compression. Meanwhile, the separation membrane was immersed in acetone and sonicated for 15 minutes to remove each coating layer and extract the porous substrate.
[0134] (1) Thickness measurement The thickness of the polymer substrate and the separation membrane were measured using a contact thickness gauge (Mitutoyo, VL50S-B).
[0135] (2) Air permeability measurement The time it took for 100 ml of air to pass through the separation membrane was measured using an Oken type air permeability measuring device (Asahi Seiko).
[0136] (3) ER (resistance measurement) An electrolyte solution was prepared by mixing ethylene carbonate and ethyl methyl carbonate in a ratio of 3:7, adding vinylene carbonate at 2 wt % relative to the solvent, and adding LiPF6 to a concentration of 1 M. The separators of each of the examples and comparative examples were immersed in the electrolyte solution and measured at 25°C using an AC method (frequency 10,000 to 100,000 Hz).
[0137] (4) Pore size distribution A sample was obtained from the center of the width of the polymer substrate of each Example and Comparative Example, measuring 5 cm in the TD direction and 5 cm in the MD direction. A dry curve was obtained for each sample obtained using a Perm-Porometer (CFP-1500A) from Porous Materials Inc. (PMI). A wet curve was obtained after filling the porous substrate with Galwick solution. The measurement pressure was in the range of 0 to 3500 MPa. The pore distribution and half-width of the polymer substrate were calculated from the above. Meanwhile, in the obtained curve, the bubble point can represent the maximum diameter of the pores, and the intersection point of the wet sample curve and the dry sample curve can represent the minimum diameter of the pores. FIG. 7 shows the air permeability curve of the dry sample and the air permeability curve of the wet sample. Referring to FIG. 7, the intersection point of the air permeability curve of the 1 / 2 dry sample, which is a value corresponding to 1 / 2 of the value of the air permeability curve of the dry sample, and the wet sample curve can represent the average value of the pore diameter.
[0138] [Table 3]
[0139] [Table 4]
[0140] [Table 5]
[0141] As can be seen from Table 5, the thickness reduction rate of the polymer-based material in the separator of the embodiment was lower than that of the comparative example. The thickness reduction rate of the porous coating layer was in a similar range between the embodiment and the comparative example. Meanwhile, the difference in the air permeability of the separator before and after compression was about 200 sec / 100 cc in the comparative example, but it was confirmed that it increased by only about 50 sec / 100 cc in the embodiment, indicating excellent compression resistance. It was confirmed that such a change also affects the resistance of the separator, and the resistance of the separator increased by more than 0.3 ohms in the comparative example, but only increased by 0.2 ohms in the embodiment. Meanwhile, according to the results of confirming the change in the porosity of the polymer-based material, the porosity increased by about 4 vol% or less in the embodiment, but the increase exceeded 10 vol% in the comparative example. As confirmed above, it was confirmed that the separator according to the present invention has an effect of improving compression resistance. [Explanation of symbols]
[0142] 10: Separation membrane 11: Polymer base material 12: Organic / inorganic composite porous coating layer 13: Adhesive coating layer
Claims
1. A porous polymer substrate; a porous organic / inorganic composite porous coating layer disposed on at least one surface of the polymer substrate; an adhesive coating layer disposed on one side of the organic / inorganic composite porous coating layer, the adhesive coating layer being the opposite side to the polymer-based material; The polymer-based material is a polymer membrane having an average pore size of 40 nm or less, and the pore distribution has a Gaussian distribution full width at half maximum (FWHM) value measured through a pore size distribution of 8.0 nm or less. The organic / inorganic composite porous coating layer includes a particulate binder resin and inorganic particles, and the particulate binder resin includes an acrylic binder resin and a PVdF binder resin. The separator for an electrochemical device, wherein the adhesive coating layer comprises a PVDF-based binder resin.
2. 2. The separator for an electrochemical device according to claim 1, wherein the polymer-based material has an air permeability of 100 sec / 100 cc or less and a resistance of 0.6 ohms or less.
3. 2. The separator for an electrochemical device according to claim 1, wherein the separator has an air permeability of 100 sec / 100 cc or less and a resistance of 0.6 ohms or less.
4. 2. The separator for an electrochemical device according to claim 1, wherein the polymer substrate has a porosity of 20 vol % to 50 vol %.
5. 2. The separator for an electrochemical device according to claim 1, wherein the organic / inorganic composite porous coating layer contains the inorganic particles and the particulate binder resin in a weight ratio of 75:25 to 90:
10.
6. 2. The separator for an electrochemical device according to claim 1, wherein the organic / inorganic composite porous coating layer has a mixture of the inorganic particles and the particulate binder resin of 99 wt % or more relative to 100 wt % of the entire layer.
7. 2. The separator for an electrochemical device according to claim 1, wherein the organic / inorganic composite porous coating layer contains the PVDF-based binder resin and the acrylic-based binder resin in a weight ratio of 30:70 to 5:
95.
8. 2. The separator for an electrochemical device according to claim 1, wherein the adhesive coating layer contains the PVDF-based binder resin in an amount of 90% by weight or more based on 100% by weight of the entire adhesive coating layer.
9. The separator for an electrochemical device according to claim 8 , wherein the PVDF-based binder resin of the adhesive coating layer has a weight average molecular weight of 600,000 or less.
10. 2. The separator for electrochemical devices according to claim 1, wherein the PVdF-based binder resin of each of the organic / inorganic composite porous coating layer and the adhesive coating layer contains, as a polymerization unit, vinylidene fluoride and a copolymer of a monomer copolymerizable with vinylidene fluoride, and the copolymer contains 70 wt % or more of vinylidene fluoride.
11. 11. The separator for an electrochemical element according to claim 10, wherein the PVdF-based binder resin has a substitution degree with the monomer of 1 wt % to 40 wt %.
12. 2. The separator for an electrochemical device according to claim 1, wherein the particulate binder resin is maintained in particulate form within the separator.
13. 2. The separator for an electrochemical device according to claim 1, wherein the adhesive coating layer has a thickness of 8% to 30% based on 100% of the thickness of the organic / inorganic composite porous coating layer.
14. An electrochemical element comprising: a negative electrode; a positive electrode; and the separator according to claim 1 interposed between the negative electrode and the positive electrode.
15. A method for producing the separation membrane according to any one of claims 1 to 13, (S10) preparing a porous polymer substrate; (S20) forming an organic / inorganic composite porous coating layer on the surface of the polymer substrate; (S30) forming an adhesive coating layer on a surface of the organic / inorganic composite porous coating layer opposite to the surface on which the polymer-based material is disposed; The step (S20) is carried out by dispersing inorganic particles and a particulate binder resin in an aqueous solvent as a dispersion medium to prepare a slurry for forming an organic / inorganic composite porous coating layer, applying the slurry onto a surface of a polymer substrate, and drying the slurry. The step (S30) is performed by dispersing a particulate binder resin in an aqueous solvent as a dispersion medium to prepare a composition for forming an adhesive coating layer, and then coating the composition on the surface of the organic / inorganic composite porous coating layer and drying the composition.
Citation Information
Patent Citations
Microporous film and separator using the same
JP2015120786A
Battery separator and nonaqueous electrolyte battery
WO2009044741A1
Separator for nonaqueous secondary batteries, and nonaqueous secondary battery
WO2014083988A1
Separator for nonaqueous secondary batteries, and nonaqueous secondary battery
WO2014147888A1
Battery, battery pack, electronic device, electric vehicle, electric storage device, and power system
WO2015056385A1